Recent Status of Arsenic Contamination in Groundwater of Nepal – A Review - Panthi, Sudan Raj; Sharma, Subodh; Mishra, Abadh Kishore (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Arsenic in ground water is becoming an emerging issue in the water supply and health sectors of Nepal. Considerably high percentages of people live in rural Terai region and most of them are dependent on hand tube wells for drinking water consumption in Nepal. The ground water in the past was considered to be safe for drinking purpose but now it came to be known that many shallow tube wells contain arsenic at concentrations higher than the safe limit set for drinking purpose by WHO 1993. This paper reviews the recent status of arsenic in ground water of Nepal and recommends proper research methods to be adopted in mitigating the effects of it to human health.